THE COMPETITIVE ADVANTAGE: INSIGHTS FROM PRIVATE UNIVERSITIES - Susilo, Wilhelmus Hary; Julius, Yudi (PEOPLE: International Journal of Social Sciences, 2019)
The private universities in a flexible system for faced the industrial 4.0 decade of being always changing in Jakarta. The marketing research has built from confirmed the model of Analysis on pursuit of a sustainable competitive advantage. The research was conducted with confirmatory strategic research design, of structural equation hybrid modeling. The hypothesis result were confirmed i.e., great interaction each other and price perception influences to superior and energizer value of consumer. The value of consumer affects to decide. Furthermore loyalty and character building lead to pursuit of a sustainable competitive advantage.